Theoretical aspects of the nature of the electronic commerce - Avakyan, G.; Serhiienko, Hanna; Сергієнко, Ганна Віталіївна; Сергиенко, Анна Витальевна (ТДАТУ, 2018)
Consequently, the development of e-commerce is becoming increasingly important in the context of globalization of economic processes, due to the possibility of achieving global presence and implementation of economic activity on a global scale, global choice of goods, regardless of the geographical position of the subjects.
Keywords: economic activity forms; economic transactions; global choice of goods; globalization of economic processes